Bilateral complete ureteral duplication in a woman with recurrent Urinary Tract Infection (UTI): case report - Figueiredo, Bárbara Queiroz de (2021)
Introduction: The ureters are bilateral thin tubular structures (3 to 4 mm) that connect the kidneys to the urinary bladder, carrying urine from the renal pelvis to the bladder. The muscle layers are responsible for the peristaltic activity that the ureter uses to move urine from the kidneys to the bladder. Objective: to present a clinical case of a patient with complete bilateral ureteral duplicity, associated with frequent episodes of urinary tract infection. Methodology: this is a clinical case study with a qualitative and descriptive perspective, which consists of a research that, in general, takes place with direct data collection, in which the researcher is the indispensable instrument. Case report: this is a female patient, 18 years old, with frequent episodes, since the age of 14, of urinary tract infections and complaints of feeling of incomplete bladder emptying, under treatment with a urologist. It is reported that after infections, the presence of constant vaginal discharge is intensified, in large quantities, with a strong odor, however, without burning. At 15 years of age, he was diagnosed with complete bilateral ureteral duplication, by means of computed tomography of the total abdomen, with subsequent intravenous administration of contrast. Conclusion: Many of the ureteral morphological changes can be evaluated using computed tomography, due to its most modern technological advances, it has contributed in recent years to a better characterization of morphological changes, being essential in the diagnosis of congenital anomalies, better guiding clinical and surgical therapeutic decisions and acting as an essential tool in identifying associated complications.